Isaac Newton and the scientific revolution - Christianson, Gale E. (New York Oxford University Press, 1996)
Explores the life and scientific contributions of the famed English mathematician and natural philosopher.
Includes bibliographical references (p. 149-151) and index.
Keywords: Newton, Isaac -- Sir -- 1642-1727 -- Biography -- Juvenile literature; Physics -- History -- Juvenile literature; Science -- History -- Juvenile literature; Physicists -- Great Britain -- Biography -- Juvenile literature